Smart waste sorter chute / Nur Syifaa Hashim and Hasni Suryani Mat Hasan - Hashim, Nur Syifaa; Mat Hasan, Hasni Suryani (2023)
High-rise buildings nowadays symbolise a country’s rapid growth. The construction of high-rise building dominates Malaysia’s economy, as it is one of the developing nations. The rapidly growing construction sector in Malaysia has produced numerous types of waste products, resulting in a negative impact on the environment and an increased amount of waste in landfills. The considerable volume of garbage produced during the construction of high-rise buildings makes waste management a crucial component in such projects. Due to the absence of a systematic approach to managing construction waste, the escalation of the building construction industry has led to a significant environmental issue concerning waste reduction. The objectives of this innovation project are to identify the suitable method for waste chutes in high-rise building construction, propose sustainable elements for waste chutes in high-rise building construction, and determine the marketability of such sustainable waste chutes in high-rise building construction.